Expression and purification of recombinant feline interferon in the baculovirus-insect larvae system - Targovnik, Alexandra Marisa (2014)
Feline interferons (FeIFNs) are cytokines with antiviral, antitumor and immunomodulatory functions used as therapeutic agents in a variety of veterinary diseases. In this work, FeIFN-α7 and FeIFN-α7xArg containing eight residues of arginine were expressed in Sf9 cells and insect larvae. At 4 days post-infection (dpi), the concentrations of FeIFN-α7 and FeIFN-α7xArg in suspension culture were (1.28 ± 0.15) × 106 U ml−1 and (1.3 ± 0.2) × 106 U ml−1 respectively. The maximum expression levels of FeIFN-α7 and FeIFN-α7xArg were (3.7 ± 0.2) × 106 U ml−1 and (3.5 ± 0.4) × 106 U ml−1 at 2 dpi in Rachiplusia nu larvae and (1.1 ± 0.2) × 106 U ml−1 and (1.0 ± 0.15) × 106 U ml−1 at 5 dpi in Spodoptera frugiperda larvae respectively. R. nu was a better host for FeIFN-α7 and FeIFN-α7xArg expression. The 8xArg tag did not affect the biological activity of FeIFN-α7 and was useful to promote the FeIFN-α7xArg adsorption on ion exchange chromatography (IEC), allowing its purification in a single step from supernatant culture and R. nu larvae. FeIFN-α7xArg was purified from the larval extract with a yield of 70% and a purification factor of 25 free of viruses. We conclude that R. nu larvae are new low-cost hosts for the expression of recombinant FeIFN-α7.